Law and the Islamization of Morocco under the Almoravids : the Fatwās of Ibn Rushd al-Jadd to the far Maghrib - Gómez-Rivas, Camilo. (Studies in the History and Society of the Maghrib, 2015)
Law and the Islamization of Morocco under the Almoravids. The Fatwās of Ibn Rushd al-Jadd to the Far Maghrib investigates the development of legal institutions in the Far Maghrib during its unification with al-Andalus under the Almoravids (434-530/1042-1147). A major contribution to our understanding of the twelfth-century Maghrib and the foundational role played by the Almoravids, it posits that political unification occurred alongside urban transformation and argues that legal institutions developed in response to the social needs of the growing urban spaces as well as to the administrative needs of the state. Such social needs included the regulation of market exchange, the settlement of commercial disputes, and the privatization and individualization of property.